Effects from education as a key factor in the process of labor forces formation in the Republic of Kazakhstan - Sedlarski, T.; Tulebayeva, A.M. (BUKETOV BUSINESS REVIEW, 2018)
The article is devoted to the problem of reforming the education systems of Kazakhstan and improvement the quality of labor forces in a market economy. Of particular relevance is the analysis of the impact of investment in education on the country’s labor forces. In the context of integration into the world economy, it is necessary to find the most appropriate scientific approaches to reforming labor forces systems by improving the analysis, planning and forecasting the trends of its development, taking into account the influence of various factors. As the analysis of the works of foreign scientists in forecasting the development of human capital in the conditions of a modern market economy shows, it is the methodology of alternative forecast scenarios that reflects the needs of strategic foresight in the context of a complex intertwining of contradictory trends in the development of the world economy and human capital. It is generally recognized that in the context of rapid and ambiguous changes, it is no longer possible to use planning methods based solely on extrapolating existing trends in economic and social development. Therefore, it is important to compare the state of labor forces to date and assess it’s level of competitiveness. Regarding Kazakhstan, the results of the regression model should be taken into account when carrying out reforms. The model shows correlation between education and the quality of labor forces.